Physicians' perceptions of mobile technology for enhancing asthma care for youth. (June 2016) - Schneider, Tali; Panzera, Anthony Dominic; Martinasek, Mary; McDermott, Robert; Couluris, Marisa; Lindenberger, James; Bryant, Carol
This study assessed physicians' receptivity to using mobile technology as a strategy in patient care for adolescents with asthma. Understanding physicians' perceived barriers and benefits of integrating mobile technology in adolescents' asthma care and self-management is an initial step in enhancing overall patient and disease outcomes. We conducted in-depth interviews with second- and third-year pediatric residents and attending physicians who oversee pediatric residents in training ( N = 27) at an academic medical center in the southeastern United States. We identified both benefits from and barriers to broader use of mobile technologies for improving asthma outcomes in adolescents. Resident physicians demonstrated greater readiness for integrating these technologies than did attending physicians. Prior to adoption of mobile technologies in the care of adolescent asthma patients, barriers to implementation should be understood. Prior to widespread adoption, such systems will need to be evaluated against traditional care for demonstration of patient outcomes that improve on the current situation.